The Livelihood Change of Fishermen Recipient Grant Program of Coalition Party In Lubuk Puding Village Buru District of Karimun Regency of Riau Islands Province - Saknah '; Hamdi Hamid; Zulkarnain Umar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in January 2016 in the village of Lubuk Puding in the District of Buru Karimun Riau Islands Province. The objective of this study was to determine the characteristics of fishing grantees, to determine changes in fishing livelihoods after receiving the grant, and to determine the relationship characteristic of changes, livelihoods and grants program. The method used in this study was survey of 160 grantees fishermen population, in which this study taken as much as 15% of the 160 populations or 24 peoples.Based on the research result, the characteristics of grant recipient are productive fishermenage, low education and the number of family member of fishermen. The livelihood of fishermen grant recipients changed from the preparatory stage to the growth stage, while in food consumption and employment on a fixed income and sanitation and hygiene unchanged. Characteristics with real changes in the livelihoods of fishermen are age which have relationship with income and with the job opportunities, the number of family member has relationship with food consumption and grant, and food consumption have relationships with the grant.Keywords: Change, Livelihoods, Fisherman.